Domino Reactions of 1-Aroyl-3,4-dihydroisoquinolines with α,β-Unsaturated Aldehydes - Matveeva, Maria D.; Borisova, Tatiana N.; Titov, Alexander A.; Anikina, Lada V.; Dyachenko, Svetlana V.; Astakhov, Grigorii S.; Varlamov, Alexey V.; Voskressensky, Leonid G. (Synthesis, 2017)
An efficient synthesis of pyrrolo[2,1-a]isoquinolines by a domino reaction from a variety of 3,4-dihydropyrrolo[2,1-a]isoquinolines and α,β-unsaturated aldehydes in the absence of catalyst in good yields under microwave irradiation, is reported.
Keywords: domino reaction; dihydroisoquinolines; aldehydes; microwave irradiation; cytotoxic activity